USE OF E -COMMERCE IN THE EDITORIAL MIKRODATA BY RELYING SITE E-BSTORE - Nur Akbar; Irwan Bastian, SKom, MMSi (Jurnal Sistem Informasi, 2001)
In today's business world has recognized the existence of the term E -Commerce, a term that describes the chance of utilizing the Internet as a means to transact business. Such opportunities have now also started to be perceived by many publishing companies through  the Internet. The population in this study were Internet users who visited the site e -BStore. The sampling method used was non -probability sampling using the Internet as the main mediator in the dissemination of questionnaire. From the results of questionnaires given suggests that the introduction and promotion of e-BStore site can only be through certain media such as magazines Info Computer, Chip, Anti -Virus & Mikrodata. In addition, they also argue that the opportunity to offer products through the Internet is vast and diverse, not only limited to certain media. In offering the product via the internet, most respondents argued that the promotion of e -BStore existence is still little known to the public, therefore the authors to optimize and analyze promotions through the media outside the internet medium, such as newspapers, seminars, magazines, radio and television, as well as facilities view e-BStore web site needed to better known mention the existence of e-BStore site to the public.